Mães enlutadas: estabelecendo laços entre a morte e o percurso do luto diante da perda de um(a) filho(a). - Suárez, Larissa de Araújo Batista (2022)
In a World full of cultural and religious experiences. it becomes vague to treat and to know about death in a uniform way. It is necessary to know the types of death and the farewell rituals that exist in different cultures and religions. With the death of a person, which is a fundamental part of the evolution of life. It is possible to elaborate and starting a grief process through the resignification of it. Each experience has different meanings, and may vary according to the mediators of grief. This article has the general objective to analyze the mediators of mourning, farewell rituals, also unconscious alliances in a group of mothers who experience the loss of a child due to early death. The group of Mother’s participate in a mutual grief help group. This research article is exploratory-descriptive, with a qualitative approach. For the data collection, we used a questionnaire/interview script directed to the participants. It was a individually and collective interview with the focus in group analysis. The content was according to Bardin's method. The sample was intentional, composed of ten mothers who lost their children. They participate in a mutual help group. The results confirmed that the the unconscious alliances were the basis of the mourning mother's psychic reality and the bonds established in the group. Additionally, mourning mediators were fundamental for the elaboration and the analysis of the evolution of maternal mourning. When considering the person who died, the nature of the bond with the bereaved, the type of death, historical background, stressors, personality variables and social variables. The Funeral rituals based on Catholicism were part of the grieving process. The ritual helped recognize the importance of the loss and the relevance of the dead person. It was possible to identify, from a kaleidoscope view of psychologies, that Psychoanalysis, Cognitive Behavioral Therapy and Logotherapy are the main psychological approaches in helping and treating patients with demands related to death and grief. Thus, it was concluded that grief mediators become a parameter to study how death can affect the mourning. Also, treatments and contracts were formed in forms of unconscious alliances between the singular and the plural as bases of balance in the face of pain, however, there were rituals necessary for each individual in the process of mourning and separation.